Endochin-Like Quinolones Exhibit Promising Efficacy Against Neospora Caninum in vitro and in Experimentally Infected Pregnant Mice - Anghel, Nicoleta; Balmer, Vreni; Müller, Joachim; Winzer, Pablo; Aguado-Martinez, Adriana; Roozbehani, Mona; Pou, Sovitj; Nilsen, Aaron; Riscoe, Michael; Doggett, J. Stone; Hemphill, Andrew (Frontiers in Veterinary Science, 2018)
We report on the efficacy of selected endochin-like quinolones (ELQs) against N. caninum tachyzoites grown in human foreskin fibroblasts (HFF), and in a pregnant BALB/c mouse model. Fourteen ELQs were screened against transgenic N. caninum tachyzoites expressing β-galactosidase (Nc-βgal). Drugs were added concomitantly to infection and the values for 50% proliferation inhibition (IC50) were determined after 3 days. Three compounds exhibited IC50 values below 0.1 nM, 3 ELQs had IC50s between 0.1 and 1 nM, for 7 compounds values between 1 and 10 nM were noted, and one compound had an IC50 of 22.4 nM. Two compounds, namely ELQ-316 and its prodrug ELQ-334 with IC50s of 0.66 and 3.33 nM respectively, were previously shown to display promising activities against experimental toxoplasmosis and babesiosis caused by Babesia microti in mice, and were thus further studied. They were assessed in long-term treatment assays by exposure of infected HFF to ELQs at 0.5 µM concentration, starting 3 h after infection and lasting for up to 17 days followed by release of drug pressure. Results showed that the compounds substantially delayed parasite proliferation, but did not exert parasiticidal activities. TEM of drug treated parasites detected distinct alterations within the parasite mitochondria, but not in other parasite organelles. Assessment of safety of ELQ-334 in the pregnant mouse model showed that the compound did not interfere in fertility or pregnancy outcome. In N. caninum infected pregnant mice treated with ELQ-334 at 10 mg/kg/day for 5 days, neonatal mortality (within 2 days post partum) was found in 7 of 44 pups (15.9%), but no postnatal mortality was noted, and vertical transmission was reduced by 49% compared to the placebo group, which exhibited 100% vertical transmission, neonatal mortality in 15 of 34 pups (44%), and postnatal mortality for 18 of the residual 19 pups during the 4 weeks follow-up. These findings encourage more research on the use of ELQs for therapeutic options against N. caninum infection.